The Actp Acetate Transporter Acts Prior to the Pita Phosphate Carrier in Tellurite Uptake by Escherichia Coli - Vasquez-Guzman, C; Arenas-Salinas, F; Elias-Bustos, A; Díaz-Vásquez, W; Abarca-Lagunas, M (Elsevier GmbH, 2015)
The tellurium oxyanion tellurite is harmful for most microorganisms. Since its toxicity occurs chiefly once the toxicant reaches the intracellular compartment, unveiling the toxicant uptake process is crucial for understanding the whole phenomenon of tellurium toxicity. While the PitA phosphate transporter is thought to be one of the main paths responsible for toxicant entry into Escherichia coli, genetic and physiological evidence have identified the ActP acetate carrier as the main tellurite importer in Rhodobacter capsulatus. In this work, new background on the role of these transporters in tellurite uptake by E. coli is presented. It was found that, similar to what occurs in R. capsulatus, ActP is able to mediate toxicant entry to this bacterium. Lower reactive oxygen species levels were observed in E. coli lacking the actP gene. Antioxidant enzyme catalase and fumarase C activity was almost unchanged after short exposure of E. coli δ. actP to sublethal tellurite concentrations, suggesting a low antioxidant response. In this strain, tellurite uptake decreased significantly during the first 5. min of exposure and inductively coupled plasma optical emission spectroscopy assays using an actP-overexpressing strain confirmed that this carrier mediates toxicant uptake. Relative gene expression experiments by qPCR showed that actP expression is enhanced at short times of tellurite exposure, while pitA and pitB genes are induced later. Summarizing, the results show that ActP is involved in tellurite entry to E. coli and that its participation occurs mainly at early stages of toxicant exposure. © 2015 Elsevier GmbH.